The way of avoiding plagiarism in academic publications - Turayeva Umida (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In order to avoid plagiarism, you need to be certain that anything you are stating without citation is your own idea. To make sure that you are properly expressing your own ideas and not the author’s, you should take careful notes on your topic and make sure you distinguish the author’s ideas from your own. You must properly cite the sources that you quote or paraphrase. There might be several problems of using AI when it comes to citing academic papers. According to Teng (2023), plagiarism is considered as “appropriation of another’s work in one’s own written work and emphasizes the inaccurateness is certain to happen when addicted to the AI”. Any time you utilize someone else’s work without giving him or her credit, you are plagiarizing. This may include copying word-for-word, changing certain words, or using another person’s ideas without properly citing him or her.